Unequal Value Capture in Non-TimberForest Product Chains with Evidence fromPine Resin Processing in Rural Indonesia - Andi Mawaddah Zakiyah; Rini Pratiwi; Astina Astina; Widyanti Utami A (Jurnal Wasian, 2026)
This study examines unequal value capture within the pine resin value chain as a locally important non-timber forest product (NTFP) in rural Indonesia (Sasaka Village, West Sulawesi Province). Using a quantitative descriptive approach, data were collected through field observations, interviews, and a census of 33 active resin tappers, complemented by information from intermediaries and processing industries. The analysis identifies three main marketing channels involving farmers, intermediaries, and a processing industry that transforms raw resin into higher-value products, namely rosin (gondorukem) and turpentine. Results show that both marketing and profit margins are highly uneven across the value chain. While farmers receive a stable price of IDR 10,000/kg, the processing industry captures the largest share of value, with margins reaching IDR 13,000/kg for rosin and IDR 63,000/kg for turpentine. Profit margins are similarly concentrated at the industrial level, particularly for turpentine (IDR 60,288/kg), reflecting economies of scale, processing capacity, and access to export markets. These findings demonstrate clear unequal value capture within the pine resin value chain, where upstream actors receive a relatively small share of the total economic benefits despite their critical role in production. This pattern indicates structural inefficiencies and imbalances in the marketing system. Strengthening farmer bargaining power, improving access to processing technologies, and promoting more equitable market linkages are essential to enhance inclusiveness and ensure the long-term sustainability of NTFP-based livelihoods.